PTU-022 Domperidone improves Completion Rate in small Bowel Capsule Endoscopy. (4th June 2013) - Dimitriadis, S; Koulaouzidis, A; Douglas, S; Plevris, J N
Abstract : Introduction: The completion rate of small bowel capsule endoscopy (SBCE) has been reported as 81.3–84.8%. 1 Aside lumenal narrowing, incomplete SBCE can be due to delayed gastric emptying, intestinal dysmotility and/or capsule battery life. Prokinetic agents are used to increase completion rate (CR) and theoretically diagnostic yield. Domperidone, an antidopaminergic agent, has not been widely used in SBCE; 2, 3 unlike Metoclopramide, it lacks extrapyramidal adverse effects. Methods: Retrospective study; to assess gastric transit time (GTT), small-bowel transit time (SBTT) and the CR of SBCE when using domperidone. Furthermore, we aimed to compare the CR of 2 different SBCE systems (MiroCam®, PillCam®). Consecutive SBCE examinations (period 2008–2012) from a tertiary referral centre in Scotland were analysed; domperidone was not administered to the first 203 patients, but was given orally to the subsequent 449, reflecting changes in clinical practise. Results: In the aforementioned period, a total of 652 SBCE examinations were performed [265 (40.6%) men and 387 (59.4%) women]; 385/652 (59%) were performed with PillCam® and 267 (41%) with Mirocam®. The most common indications for SBCE were obscure gastrointestinal bleeding, anaemia, Crohn's disease (known or suspected) and abdominal pain. In 449/652 (68.9%) liquid domperidone (5 mg) was administered for capsule ingestion, while in 203 (31.1%) the capsule was ingested without any domperidone. In our series, the overall CR of SBCE was 86.7%. The 2 SBCE systems showed equivalent CR (PillCam ® 87.5%, MiroCam ® 85.4%; P = 0.43). The use of domperidone increased CR (88.6% vs 82.3%, P = 0.027). A higher CR was noted when domperidone was used with PillCam ® in contrast to MiroCam ® (82.2 vs 92.5%, P = 0.002 and 83.3 vs 85.5% respectively, P = 0.8). Furthermore, the median GTT and the median SBTT did not differ between the two groups (GTT/SBTT with Domperidone 27.0'/222.0' and without 30.5'/228.0', respectively; P = 0.436/ P = 0.477).The median age of patients who received domperidone was higher compared with patients who did not receive (58y vs 48y, P = 0.009), although CR was not affected by the age (complete: 55 y, incomplete: 61 y, P = 0.331). Conclusion: The use of Domperidone increases the CR of SBCE with PillCam®, although it does not affect the GTT and SBTT and should be routinely used to improve CR in SBCE with PillCam®. Disclosure of Interest: S. Dimitriadis: None Declared, A. Koulaouzidis Grant/Research Support from: Given Imaging Ltd, S. Douglas: None Declared, J. Plevris: None Declared References: Liao Z, et al. Indications and detection, completion and retention rates of small-bowel capsule endoscopy: a systematic review. Gastrointest Endosc 2010; 71:280–6. Westerhof J, et al. Diagnostic yield of small-bowel capsule endoscopy depends on the small-bowel transit time. World J Gastroenterol 2012; 18:1502–07. Keuchel M, et al. Domperidone shortens gastric transit time of video capsule endoscope. Endoscopy 2003; 35(Suppl. II):A185.